Role and efficacy of verbal imagery in the teaching of singing: Case study and computer vocal analysis - Chen, Ti-Wei (Saarbrücken VDM Verlag Dr. Müller, 2007)
Voice teachers and vocal pedagogical literature cite verbal imagery, e.g. "sing as if you are biting an apple", as a commonly used teaching tool for convey?ing desirable physical sensations, musical interpretations, concepts of vocal production and appropriate vocal quality. While both practitioners and re?searchers consider verbal imageries to be a fundamental means of communi?cation in contemporary vocal pedagogy, there apparently is no identified systematic research on verbal imagery in this field. The purpose of this study is to examinie the role and efficacy of verbal imagery in vocal pedagogy based on the use of observations and interviews of selected voice teachers and computer vocal analysis of selected undergraduate vocal students. Utilizing these two seemingly disparate research approches offers the advantages of obtaining data and insights based on the pedagogical wisdom and practical experience of voice teachers along with the technical objectivity of computer vocal analysis. The book is addressed to voice teachers and students, vocal coaches and general music educators. It is also aimed towards researchers in vocal pedagogy, music education and psychology of learning.